Řešení sudoku pomocí kvantového počítání - Saji, Deepthy (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2025)
In this thesis, Sudoku is solved by the well-known quantum algorithms. The algorithms used are Grover’s algorithm and quantum counting that uses quantum phase estimation. The grid size of the Sudoku is varied to study the impact on the quantum hardware such as Qiskit while performing quantum computation to solve the Sudoku using these algorithms. Furthermore, this thesis explores an alternative implementation pathway for these Sudoku-solving quantum algorithms using Clifford algebra, offering insights into the improvement of resources for quantum computation.

In this thesis, Sudoku is solved by the well-known quantum algorithms. The algorithms used are Grover’s algorithm and quantum counting that uses quantum phase estimation. The grid size of the Sudoku is varied to study the impact on the quantum hardware such as Qiskit while performing quantum computation to solve the Sudoku using these algorithms. Furthermore, this thesis explores an alternative implementation pathway for these Sudoku-solving quantum algorithms using Clifford algebra, offering insights into the improvement of resources for quantum computation.
Solving sudoku by quantum computation
Keywords: Quantum computation; Grover’s algorithm; Quantum phase estimation; Quantum Register Algebra.; Quantum computation; Grover’s algorithm; Quantum phase estimation; Quantum Register Algebra.